Answer:
m = (y2 - y1) / (x2 - x1) | * (x2 - x1)
m * (x2 - x1) = y2 - y1 | + y1
m * (x2 - x1) + y1 = y2
Answer D is correct.
QUESTION 1a.
We want to add
We group similar terms to get
Simplify:
QUESTION 1b.
The given function is:
Expand the parenthesis to obtain,
Group similar terms,
Simplify:
QUESTION 2
The given function is
The zeros of this function is given by;
Split the middle term.
Factor;
Answer:
No
Step-by-step explanation:
No, the law of sines cannot be used to solve the triangle. The triangle shows the measures of two sides and an included angle. To use the law of sines, you need to know the measure of an angle and its opposite side.
Answer On Edg. 2020
Answer:
(-3,4)
(-1,4)
(-3,7)
Step-by-step explanation:
(1,1) → (1-4, 1+3) → (-3,4)
(3,1) → (3-4, 1+3) → (-1,4)
(1,4) → (1-4, 4+3) → (-3,7)